2016
DOI: 10.3390/diseases4010014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Bioactive Compounds on Mitochondrial and Metabolic Flexibility

Abstract: Metabolic flexibility is the capacity of an organism to adequately respond to changes in the environment, such as nutritional input, energetic demand, etc. An important player in the capacity of adaptation through different stages of metabolic demands is the mitochondrion. In this context, mitochondrial dysfunction has been attributed to be the onset and center of many chronic diseases, which are denoted by an inability to adapt fuel preferences and induce mitochondrial morphological changes to respond to meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 64 publications
2
25
0
1
Order By: Relevance
“…6e). Similar effect on the mitochondrial index has been induced by other flavonoid such as resveratrol, which has been shown to promote an increase in mitochondrial numbers in liver and kidney of mice [79]. VCN-2-treated groups also had a lower nucleo-cytoplasmic ratio (Fig.…”
Section: Discussionsupporting
confidence: 63%
“…6e). Similar effect on the mitochondrial index has been induced by other flavonoid such as resveratrol, which has been shown to promote an increase in mitochondrial numbers in liver and kidney of mice [79]. VCN-2-treated groups also had a lower nucleo-cytoplasmic ratio (Fig.…”
Section: Discussionsupporting
confidence: 63%
“…In recent years, some studies have demonstrated that food bioactive compounds are able to enhance mitochondrial spare respiratory capacity . Taking this in mind, we evaluated in C2C12 myoblasts the potential positive effect of YM on mitochondrial function, and we showed that YM was able to increase the mitochondrial spare respiratory capacity at doses of 150 and 200 μg mL −1 in these cells.…”
Section: Discussionmentioning
confidence: 91%
“…Sleep disruption (discontinuity of sleep) can lead to the disruption of circadian rhythms 13 , which orchestrate crucial physiological and behavioral functions, being one of these the regulation of carbohydrate and fatty acid metabolism 12 . Higher sleep duration and quality are associated with a healthier gut microbiome 53 , which could suppress insulin signaling, increase β-oxidation and inhibit fat oxidation derived from the production of short-chain fatty acids 54 . Furthermore, sleep disruption (discontinuity of sleep) could decrease melatonin production 13 , which has important metabolic functions, such as lipolysis, regulating the energy flow 55 .…”
Section: Discussionmentioning
confidence: 99%